2014
DOI: 10.1097/gme.0b013e31829e4a35
|View full text |Cite
|
Sign up to set email alerts
|

Oral estrogen therapy may mitigate the effects of aerobic training on cardiorespiratory fitness in postmenopausal women

Abstract: Oral estrogen therapy may mitigate the cardiorespiratory fitness increase induced by aerobic training in hysterectomized healthy postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…One study evaluated the combination of resistance training and AT ( 33 ) and the others investigated the effects of AT ( 34 - 39 ). The HRT used was orally administered and included estradiol valerate ( 36 - 39 ), unopposed estrogen, and/or progestins ( 33 - 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study evaluated the combination of resistance training and AT ( 33 ) and the others investigated the effects of AT ( 34 - 39 ). The HRT used was orally administered and included estradiol valerate ( 36 - 39 ), unopposed estrogen, and/or progestins ( 33 - 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (71%) reported results related to physical fitness. These included AT performed 3 times a week with moderate intensity and oral HRT with 1 mg/day estrogen ( 36 , 37 , 39 ) or 0.625 mg/day equine conjugated estrogen ( 34 ) for 26 weeks. Only one trial included five weekly training sessions, with 1 mg/day oral estrogen for 12 weeks ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations